2007
DOI: 10.1002/pd.1750
|View full text |Cite
|
Sign up to set email alerts
|

ADAM 12 as a second‐trimester maternal serum marker in screening for Down syndrome

Abstract: Background ADAM 12 is a placenta-derived glycoprotein that is involved in growth and differentiation. The maternal serum concentration of ADAM 12 is a potential first-trimester maternal serum marker of Down syndrome (DS). Here we examine the potential of ADAM 12 as a second-trimester maternal serum marker of DS. Materials and MethodsThe concentration of ADAM 12 was determined in gestational week 14-19 in 88 DS pregnancies and 341 matched control pregnancies. Medians of normal pregnancies were established by po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The low ADAM12 results confirm the early observations of Laigaard et al [17] who demonstrated in a small series of 10 cases that prior to 55 days, levels of ADAM12 were less than the detection limit of the assay and increased as the gestational age increased. This mirrors the temporal pattern that has been described for ADAM12 in pregnancies with trisomy 21 [19,20], and is similar to that described for PAPP-A [31,32], which like ADAM12 is another IGFBP protease [13,33]. However the temporal pattern is unlike that seen for PAPP-A in trisomy 18 when the low levels of PAPP-A in the first trimester are even further reduced in the second trimester [6,34,35].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The low ADAM12 results confirm the early observations of Laigaard et al [17] who demonstrated in a small series of 10 cases that prior to 55 days, levels of ADAM12 were less than the detection limit of the assay and increased as the gestational age increased. This mirrors the temporal pattern that has been described for ADAM12 in pregnancies with trisomy 21 [19,20], and is similar to that described for PAPP-A [31,32], which like ADAM12 is another IGFBP protease [13,33]. However the temporal pattern is unlike that seen for PAPP-A in trisomy 18 when the low levels of PAPP-A in the first trimester are even further reduced in the second trimester [6,34,35].…”
Section: Discussionsupporting
confidence: 79%
“…In a larger series of first trimester cases [19] and a similar larger series of second trimester cases [20] with trisomy 21 it has been confirmed that first trimester levels of ADAM12 are reduced and that the reduction is more pronounced in earlier gestation. Discrimination appears best around 8-10 weeks, decreasing slightly at 12-14 weeks, and then as ADAM12 levels increase in trisomy 21, discrimination improves yet again at around 16 weeks.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Later studies, using a new DELFIA platform (PerkinElmer Life Sciences, Turku, Finland), supported these early results, placing the discriminatory power of ADAM-12 greatest prior to 10 weeks' gestation [21][22][23][24][25] . In the second trimester, ADAM-12 levels were found to be increased in trisomy-21 pregnancies [26,27] .…”
Section: Adam-12 In Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…These include various cancers [27,51,52,53,54,55,56,57,58,59], liver fibrogenesis [60], cardiac hypertrophy [61], and asthma [62]. There is also evidence to suggest that increases in ADAM12 are associated with adverse outcomes in pregnancy [63,64,65], and that it may also be used as a first [66] or second [67,68] trimester screen for Down syndrome, although these data are considerably more debated. Given these, it is suggested that discerning the molecular basis of the ADAM12 assisted disease progression would lead to improved selection of therapeutic options and possibly individualized therapy of patients.…”
Section: : Adam12mentioning
confidence: 99%